Pengembangan Model Database Petani Tingkat Kecamatan untuk Menunjang Program Pemberdayaan Petani - Muhammad Tassim Billah (Politeknik Pembangunan Pertanian Bogor, 2020)
In order to increase production and improve the welfare of farmers, the government through the ministry of agriculture and other relevant ministries, annually distributes a variety of assistance to farmers in the form of input subsidies such as fertilizer and direct assistance in the form of seed assistance and agricultural machinery and other forms of aids. To ensure that all assistance is channeled and received appropriately by farmers, accurate data is needed on the number of farmers and their farming conditions. Agricultural extension workers are also expected to have valid data about farmers in their working area, so that they can program counseling well and on target. In order to equip agricultural extension officers with valid and accurate farmer data, as well as providing a farmer database for policy making purposes, it is necessary to develop a farmer database system that can be updated and accessed quickly. For this purpose, Bogor Agricultural Development Polytechnics through lecturer research activities carried out at BPP (sub-district level) and Distan (district level), designed a farmer database model that was implemented in 2016. The development of the Farmers Database System model was designed using an approach of Database Systems Development Lyfe Cycle (Connoly, 2014) with some adjustments. It is hoped that later a valid kecamatan level of farmer database will be used as a reference in making various decisions related to farmers.This paper outlines the concept of a farmer database system model design, possible implementations, constraints, and challenges that will be encountered in its later operation. The output of this research is a complete database design of farmer databases ready to be further developed into a software application by a programmer/developer. For future implementation, it is expected that BPPSDMP can initiate the project. Â Dalam rangka peningkatan produksi dan peningkatan kesejahteraan petani, pemerintah melalui kementerian pertanian dan kementerian terkait lainnya, setiap tahun menyalurkan berbagai bantuan kepada petani baik dalam bentuk subsidi input seperti pupuk dan bantuan langsung berupa bantuan benih dan alat mesin pertanian maupun dalam bentuk lain. Guna memastikan bahwa seluruh bantuan tersebut tersalur dan diterima dengan tepat oleh para petani, makaÂ diperlukan data yang akurat tentang jumlah petani dan kondisi usahataninya.Â Para penyuluh pertanian juga diharapkan memiliki data yang valid tentang petani yang ada di wilayah kerjanya, sehingga dapat memprogramkan penyuluhan dengan baik dan tepat sasaran. Guna melengkapi petugas penyuluh pertanian dengan data petani yang valid dan akruat, serta menyediakan database petani bagi kepantingan pengambilan kebijakan, maka perlu disusun suatu sistem basisdata petani yang dapat di update dan diakses dengan cepat. Untuk keperluan tersebut, STPP/Polbangtan Bogor melalui kegiatan penelitian dosen yang dilaksanakan di BP3K/BPP (kecamatan) dan BP4K/Distan (kabupaten), mendesain suatu model database petani yang telah dilaksanakan dalam tahun 2016. Diharapkan nantinya database petani tingkat kecamatan yang valid akan dapat dijadikan acuan dalam pengambilan berbagai keputusan terkait petani. Makalah ini menguraikan konsep desain model sistem database petani, kemungkinan implementasinya, kendala, dan tantangan yang akan dihadapi dalam pengoperasiannya nanti. Output dari penelitian ini adalah rancangan lengkap database petani yang siap dikembangkan lebih lanjut menjadi suatu software aplikasi oleh programmer/developer. Untuk implementasinya kedepan diharapkan BPPSDMP dapat memprakarsainya.